Continuous meteorological observations at the Naples extquotesingles harbor weather station (Naples, Italy) during the period Jan. 2022 - Dec. 2022 - Alberto Fortelli; Fabio Matano; Marco Sacchi (PANGAEA, 2023)
Weather data monitoring is ongoing since 2013 in a network of four sites located in the metropolitan area of Naples (Italy) in the framework of the MONICA (Innovative Monitoring of Coastal and Marine Environment) Project. The aim of this activity is to acquire time series to analyze the influence of meteorological factors on geomorphological coastal processes, such as cliff retreat, landslides and beach erosion. To this three sites has been added a new monitoring site in the Port of Naples, to delimit to the east the overall monitoring area. The uploaded dataset includes various meteorological parameters (temperature, relative humidity, wind, barometric pressure and rain) acquired at the Naples extquotesingles harbor automatic weather station (model: DAVIS Vantage Pro2 wireless) during the period Jan. 2022 - Dec. 2022. Automatic data transfer from the weather station to the ISMAR-CNR processing center of Naples is performed by an internet LAN connection.